Simulation of diffusion mechanism of noble metal atomic layer deposition - Kwan, Jian Fu (Nanyang Technological University, 2021)
Computational methods act as a bridge between experiment and theory. They have been widely used for noble metals because noble metals play an important role in oxidation, reduction and hydrogenation reactions. Computational methods made it possible to predict the physical properties and microscopic interactions in noble metals. Computational methods include density functional theory (DFT) and they consist of two types of exchange-correlation functionals - local density approximation (LDA) and generalized gradient approximation (GGA). The objective of this project is to find the most appropriate combinations of substrate-film with the 5 noble metals. First-principles calculations based on DFT have been used to investigate the ideal functional method (PW91 or PBE), lattice and electronic structures, and the diffusion mechanism for the different noble metals (Pt, Pd, Ir, Rh, Ru). Functional method, PW91, is predicted to be the ideal method from the final energy at individual suitable cut-off energy and KPOINT. At temperature = 0 K, 6 substrate layers are determined from the final adhesion energy through cleaving surfaces of (111) and (001) on the respective noble metals. Results will be used to analyze the adhesion correlations between the noble metals, ultimately achieving the ideal arrangement of the 5 noble metals based on cohesive energy in atomic layer deposition process, thus forming an alloy.